Certainties and myths in Education - Latorre Ariño, Marino (2017)
This article aims to identify and describe some common beliefs—truths—and myths or misconceptions in the collective imagination of teachers and society in general. Both these beliefs and myths have been compared with those of educational theorists and confirmed by my own pedagogical experience over decades of teaching in primary and higher education. I describe twelve beliefs and nine myths to emphasize the positive aspects of pedagogical intervention and reveal the errors made in the desire to stay current with pedagogical innovations. The first two beliefs are essential: “Without understanding there is no learning”—meaningful learning—and “learning is acquired by doing what needs to be learned”—functional learning. Regarding myths in education, I would point out, among others, "the pedagogical value of the lecture," the belief that "memorization exams measure learning," "the more technology in the classroom, the more learning," and "the use of the multiple intelligences palette as a pedagogical methodology."